FAKTOR – FAKTOR PERUBAHAN SOSIAL YANG MEMPENGARUHI PEMBAGIAN HARTA WARISAN DI BANDA ACEH, INDONESIA - Zulham Wahyudani; Muhammad Firdaus (Program Studi Magister Ekonomi Syariah UIN Ar-Raniry, 2022)
This thesis generally discussed the social change and its relationship to the practice of Islamic inheritance within the Acehnese community, especially those who live in Banda Aceh city. This study aims to investigate the impact of the social change in altering the inheritance law. Data for this study were primarily gathered through questionnaire surveys. In addition, secondary data were gathered through various Islamic literatures, books, articles, seminar papers and other related materials. The questionnaires were distributed to 230 respondents that were randomly chosen among Banda Aceh community. The findings of this study revealed that the social change has influence on the altering of the Islamic inheritance law within the community. The data shows that the practices of inheritance in Banda Aceh were mostly based on family approval. These practices were influenced by several of social change’s factors, such as role of wives in earning family income, economy, gender, justice and traditions. As this study has several limitations, it was recommended that future studies need to examine this matter more comprehensively due to some deficiencies in its application such as the use of fiqh and ushul methods.